Deskripsi Kesulitan Pemecahan Masalah Matematika Siswa Ditinjau dari Adversity Quotient - Amirullah; Usman Mulbar; Nurwati Djam’an (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2019)
This research aims to know the difficulties of mathematical problem solving of climbers (high AQ), campers (moderate AQ), and quitters (low AQ). The type of this research is qualitative research with descriptive approach. Subjects of this research are students of class VII Junior High School in Makassar, academic year 2017/2018. Retrieval of the subject is performed by providing questionnaire ofAQ. From the results of the questionnaire, categorize the subject by type of AQ. Then giving the test of mathematical problem-solving. After giving the test, selected purposively three subjects based on climbers student (high AQ), campers (moderate AQ), and quitters (low AQ) to be interviewed. The results of the research show: 1) Climbers subject experience a little more difficulty in problem-solving compared to campers subject and quitters subject. Climbers subject experiences two difficulties in working the test of mathematical problem solving that are the conceptual difficulty and operational difficulty. 2) Campers subject experience a little more difficulty in problem-solving than quitters subject. Campers subject experience three difficulties in working the test of mathematical problem solving that are the conceptual difficulty, principle difficulty, and operational difficulty. 3) Quitters subject experience the most difficulty in problem-solving. Quitters subject experience four difficulties in working the test of mathematical problem solving that are the conceptual difficulty, principle difficulty, operational difficulty, and careless difficulty.